Post fire flexural behavior of mild steel based cold-formed built-up beams exposed to elevated temperature - Sam, Varun Sabu; Anand, N.; Abdallah, Mirvat; EI Hachem, Chady; Azab, Marc; Andrushia, Diana (Frontiers in Built Environment, 2024)
The use of back-to-back built-up channel beams in cold-formed steel (CFS) structures is steadily rising. The growing demand for CFS sections as a cost-effective design solution has driven the development of these CFS built-up sections. Despite this, there has been limited research on the performance of mild steel (MS) based CFS at high temperatures, particularly regarding its flexural behavior. This study thoroughly explores the behavior of MS-based CFS beams with different spans under high temperatures, followed by cooling with air or water. It assesses the impact of thermal loading and evaluates the effectiveness of these cooling methods. Experimental findings are validated and analyzed in conjunction with Finite Element Modeling (FEM) using ABAQUS and the Direct Strength Method (DSM). The study also conducts a parametric analysis to determine how the varying span that affects flexural capacity of beam. Among beams heated to the same temperature, those cooled with water exhibit slightly lower load capacities than those cooled with air. The maximum load observed is 91.21 kN for the reference specimen, while the minimum load is 39.82 kN for the specimen heated for 90 min and cooled with water, resulting in a 78.45% difference between these values. Additionally, as heating duration increases, ductility of beam also increases. Various failure modes are observed based on different heating and cooling conditions across different beam spans. This study offers valuable insights into the performance of MS-based CFS beams under thermal stress and different cooling conditions, providing important data for structural design and safety in construction.